Neoplatonic saints : the lives of Plotinus and Proclus by their students - Edwards, Mark W., 1929-2016; Edwards, Mark W., 1929-2016 (Translated texts for historians ;, 2000)
These two texts are fundamental for the understanding not only of Neoplatonism but also of the conventions of biography in late antiquity. Neither has received such extensive annotation before in English, and this new commentary makes full use of recent scholarship. The long introduction is intended both as a beginner's guide to Neoplatonism and as a survey of ancient biographical writing.